Different Development Forms of Local Allergic Rhinitis towards Birch. (5th June 2020) - Bozek, Andrzej; Winterstein, Janne; Galuszka, Beata; Jarzab, Jerzy
Abstract : Background . Efficacy of allergen immunotherapy (AIT) in local allergic rhinitis (LAR) is a new subject of research. The presence of asthmatic symptoms in patients with LAR in the context of AIT is unexplored. Objective . The efficacy and safety of AIT in patients with LAR towards birch pollen were investigated. The possibility of concomitant local allergic asthma in studied patients and the impact of AIT on it were examined. Methods . 36 patients with LAR towards birch were included in three years of AIT in a double-blind, placebo-control study. Primary outcome measurement was the mean changes in the combined symptom and medication scores (CSMSs) after AIT, and the second is the changes in the quality of life (QoL). Skin prick tests, serum, nasal allergen-specific IgE to birch, nasal and bronchial provocation challenge tests with birch allergen, methacholine tests, and spirometry were carried out at baseline and after AIT. Results . Mean CSMSs of three years of AIT were significantly decreased in the active group from 5.88 (range: 4.11-9.01) to 1.98 (range: 1.22-4.51; p < 0.05 ). After three years of AIT, there was a significant increase of toleration for birch allergen from the mean concentration of 6250 ± 1200 SQ-U/ml up to 45000 ± 2500 SQ-U/ml (p = 0.02 ) during repeated nasal challenges. 16 patients with LAR had the positive results of methacholine tests, and 11 of them had a positive bronchial challenge to birch allergen. After AIT, the significant decrease of bronchial responsiveness to birch allergen in 5 from 7 patients was confirmed (p = 0.03 ). QoL assessed by the use of the RQLQ score was improved after AIT from 1.84 (95% CI: 1.53-1.97) to 1.45 (95% CI: 1.32-1.62) score in the active group after three years of AIT therapy (p = 0.03 ). Conclusion . AIT to birch can be useful and safe in a patient with local allergic rhinitis and also with concomitant asthmatic symptoms. Further studies are needed.